A mathematical study on "additive technique" versus "branch and bound technique" for solving binary programming problem - Sufahani, Suliadi Firdaus; Kamardan, M. Ghazali; Rusiman, Mohd Saifullah; Mohamad, Mahathir; Khalid, Kamil; Ali, Maselan; Khalid, Kamal; Nawawi, M. K.M.; Ahmad, Asmala (2018)
A solid body needs adequate supplements from nourishment that we eat each day. Eating pretty much than what our body needs will prompt lack of healthy sustenance (under-nourishment and over-nourishment). In Malaysia, a few reviews have been directed to examine the wholesome status of Malaysians, particularly among youngsters and youths. However there are different methods for taking care of the menu arranging issue and in this paper Binary Programming (BP) is executed. Separately, "Additive Technique (AT)" and "Branch and Bound Technique (BBT)" are utilized as a part of BP. Both methodologies utilize diverse systems and might yield distinctive ideal arrangements. Along these lines, this study expects to build up a scientific model for eating regimen arranging that meets the essential supplement admission and look at the outcomes yield through additive substance and branch and bound methodologies. The information was gathered from different all inclusive schools and furthermore from the Ministry of Education. The model was illuminated by utilizing the Balas Algorithm through AT and Binary Programming through BBT.